Self –efficacy, academic achievement and happiness - Yahyanezhad, Farshid; Moharer, Ali (International Journal of Education and Cognitive Sciences, 2022)
Introduction: Happiness is a multifaceted construct that has recently been the subject of growing attention in the field of positive psychology and researchers have strived to identify its underlying factors. The search for happiness can be said to underlie all human behaviors. So, the aim of the present study is to investigate the relationship between self-efficacy, academic achievement and happiness of students and to examine the moderating role of gender in the relationship of the study variables. Materials and method: self-efficacy and happiness scale was distributed among 200 university students of Bojnourd (100 female and 100 male students) who had been selected randomly. The average score of the last academic year of the students was considered as the measure of their academic achievement score. The reliability and validity of the scale were evaluated respectively through test-retest coefficient and factor analysis and correlation of the total score with the subscales.Results: The results established the psychometric properties of the scale. For data analysis, the Pearson correlation coefficient and regression analysis were used. Only happiness was able to predict self-efficacy. Also, the moderating role of gender was approved, and only in the group of male student both efficacy variables (positive and significant) and academic achievement (negative and significant) were able to predict happiness.Conclusion: The results showed that the self-efficacy could predict happiness in both male and female students, whereas happiness was a predictor of academic achievement only in male students.